Towards a durable high performance anode material for lithium storage: stabilizing N-doped carbon encapsulated FeS nanosheets with amorphous TiO2. Issue 27 (1st July 2019) - Xie, Xuefang; Hu, Yang; Fang, Guozhao; Cao, Xinxin; Yin, Bo; Wang, Yaping; Liang, Shuquan; Cao, Guozhong; Pan, Anqiang
Abstract : In situ formed hierarchical FeS nanosheets supported by a TiO2 /C fibrous backbone exhibit higher rate capability and cycling stability as anode materials for lithium ion batteries. Abstract : As a promising conversion-type anode material, iron sulfide has been widely studied. However, due to its huge volume expansion during repeated lithiation/delithiation, iron sulfide tends to pulverize and form aggregates upon cycling, which greatly hinders its application in high performance lithium ion batteries as a durable anode material. Herein, a strategy for synthesizing and stabilizing iron sulfide nanosheets with a robust titanium oxide nanofiber interior support is proposed. The hierarchical nanostructured composite anode material was successfully synthesized by the electrospinning technique and subsequent sulfurization. The size of the iron sulfide nanosheets can be easily tuned by adjusting the composition of the reacting agents and/or the sulfurization temperature. Electrochemical results reveal that the composite delivers a reversible capacity of 591 mA h g −1 at a current density of 0.1 A g −1 after 100 cycles and exhibits excellent long-term cycling stability at 0.5 A g −1 and 1 A g −1 as well. Furthermore, when being paired with LiFePO4, the as-synthesized composite also delivers promising full-cell performance, showing its potential in serving as a competitive candidate anode material in lithium-ion batteries for power applications. Moreover, this method also opens up an avenue for modifying and improving other conversion-type anode materials.